_(ツ)_/ - Garrido, Marian (Re-visiones, 2024)
A ghost is floating around the Internet: nihilism. From the corporations, trying to grab their slice of the users’ hideouts of resistance, to collaborative platforms for consulting information, we can find numerous examples which challenge control but also threaten to derail the logic system which rules over the tangible world. Nothing matters in the virtual abyss